The Relationship between Parents' Attention and Bullying Behavior during the Covid-19 Pandemic - Dewi Aswira Putri; Yeni Karneli (Jurnal Neo Konseling, 2021)
Bullying is an act of violence that is carried out on purpose to hurt another person and cause physical or mental injury to the victim. During the Covid-19 pandemic, students should have little chance of being accepted by the environment, because at this time someone is required to maintain a distance (physical distancing) to reduce the rate of spreading the virus so quickly. This of course will make it difficult for students to carry out negative behavior towards schools, but in reality there are still students who bully others and ignore any restrictions that are around them. Many things affect bullying behavior that occurs, one of the factors that is suspected is the attention given to the home. This study aims to describe the level of parental attention, bullying behavior during the Covid-19 pandemic, and how the relationship between parents who pay attention to bullying behavior during the Covid-19 pandemic. This research is a descriptive correlational study, with a research sample of 293 students of SMAN 1 Sitiung registered in the 2020/2021 school year which is divided into 9 classes. The results of this study are (1) the attention of parents at SMAN 1 Sitiung is in the good category, (2) bullying behavior during the Covid-19 pandemic at SMAN 1 Sitiung is in the very low category, and (3) there is a significant negative relationship between pay attention to behavior with bullying behavior during the Covid-19 pandemic.